Switch to an everolimus-facilitated cyclosporine A sparing immunosuppression improves glycemic control in selected kidney transplant recipients - Kälble, Florian; Seckinger, Jörg; Schaier, Matthias; Morath, Christian; Schwenger, Vedat; Zeier, Martin; Sommerer, Claudia (Clinical transplantation, 2017)
Background: Mammalian target of rapamycin inhibitors (mToRi) allow calcineurin inhibitor (CNI) sparing therapy in renal transplant recipients with possible beneficial effects on the long-term allograft function and cardiovascular risk. The influence of mToRi on glucose metabolism is still under discussion. Methods: In a retrospective analysis, renal allograft recipients switched from a cyclosporine A (CsA) to an everolimus (EVR)-based immunosuppression in the first year after transplantation were compared with patients on continued CsA treatment. At 6-month intervals, the prevalence of impaired fasting glucose (IFG) and new onset of diabetes after transplantation (NODAT) were assessed. Results: A total of 146 renal transplant recipients were included. The cumulative prevalence of IFG and NODAT 30-months post-transplantation was significantly lower in patients switched to an immunosuppression with EVR compared to patients on continued CsA treatment (10% vs 22%, P=.049). However, patients switched to EVR showed a higher incidence of acute cellular rejections in the first 12 months (23% vs 11%, P=.048). Conclusion: EVR-based immunosuppression was associated with a similar or even improved glycemic control and improved renal function. However, due to higher rejection rates, patients switched to EVR should be carefully selected as rejection therapy with steroids counteracts the benefit in glycemic control.